2021
DOI: 10.1177/10901981211052241
|View full text |Cite|
|
Sign up to set email alerts
|

Barriers to Healthy Eating and Diabetes Diet Education: Divergent Perspectives of Patients and Their Providers

Abstract: Patients report that adhering to diet is the most challenging aspect of diabetes management. Provision of diet education is often delegated to health care providers, despite a lack of nutrition education and training and limited awareness of environmental and cultural challenges faced by patients. Aim. We examined perceived barriers to diet self-management among low-income minority patients with type 2 diabetes and their health care providers within a single ecosystem, to test whether providers understood pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For example, the participants facilitated social support by encouraging family participation. Like this study, others have reported both supportive and discouraging effects of family involvement in diabetes management in Africa, and other parts of the world ( Abdulrehman et al, 2019 ; Bross et al, 2022 ; Chepulis et al, 2021 ; Mogre et al, 2019 ; Othman et al, 2022 ; Suglo, & Evans, 2020 ; Werfalli et al, 2020 ), necessitating the need for not only involving families in patient education but also educating them on how to prevent diabetes for themselves, as well as how to support a family member living with diabetes ( Thirsk & Schick-Makaroff, 2021 ).…”
Section: Discussionmentioning
confidence: 67%
“…For example, the participants facilitated social support by encouraging family participation. Like this study, others have reported both supportive and discouraging effects of family involvement in diabetes management in Africa, and other parts of the world ( Abdulrehman et al, 2019 ; Bross et al, 2022 ; Chepulis et al, 2021 ; Mogre et al, 2019 ; Othman et al, 2022 ; Suglo, & Evans, 2020 ; Werfalli et al, 2020 ), necessitating the need for not only involving families in patient education but also educating them on how to prevent diabetes for themselves, as well as how to support a family member living with diabetes ( Thirsk & Schick-Makaroff, 2021 ).…”
Section: Discussionmentioning
confidence: 67%
“…Research supports that individuals with diabetes who are motivated to eat healthily may consume unhealthy foods because they are unable to afford healthy alternatives. 50 Providing relevant DSMES to address challenges to self-management when resources are limited is critical to future Food Is Medicine interventions.…”
Section: Effectivenessmentioning
confidence: 99%
“…People with diabetes report that the most challenging aspect of diabetes management is adherence to dietary advice, and lack of adherence is often judged by health professionals as inadequacy. 34 However, other barriers to translating individualised, person-centred, evidence-based guidelines exist and include the knowledge and experience of dietitians and primary care health professionals, and the environment.…”
Section: Translating Diabetes Nutritional Guidelines To Clinical Prac...mentioning
confidence: 99%
“…It seems to be the case that the majority of dietary intervention trials show evidence of efficacy, whatever the specific intervention, and in the absence of head‐to‐head trials there is limited evidence for one particular dietary strategy. People with diabetes report that the most challenging aspect of diabetes management is adherence to dietary advice, and lack of adherence is often judged by health professionals as inadequacy 34 . However, other barriers to translating individualised, person‐centred, evidence‐based guidelines exist and include the knowledge and experience of dietitians and primary care health professionals, and the environment.…”
Section: Translating Diabetes Nutritional Guidelines To Clinical Prac...mentioning
confidence: 99%